Drug-eluting stents versus bare-metal stents for intracranial atherosclerotic stenosis: a systematic review and meta-analysis - Yan Ma; Liqun Jiao; Tao Wang; Bin Yang; Jie Wang; Jichang Luo; Renjie Yang; Wenlong Xu; Haozhi Gong (BMJ Open)
Background In-stent restenosis (ISR) is the primary cause of stroke recurrence after intracranial stenting. Drug-eluting stents (DES) have recently shown great potential for reducing restenosis. This systematic review aimed to evaluate the efficacy and safety of DES compared with bare-metal stents (BMS) for intracranial atherosclerotic stenosis (ICAS).Methods We systematically searched the MEDLINE (Ovid), Cochrane Central Register of Controlled Trials, Embase (Ovid) and Web of Science databases for studies published from inception through 10 October 2023, comparing DES with BMS for the treatment of symptomatic severe ICAS. We included randomised controlled trials and cohort studies that compared DES and BMS in adult patients with ICAS. The primary outcomes were stroke or death within 30 days and ISR within 1 year. Secondary outcomes included procedure-related adverse events, technical success, functional evaluation findings, restenosis degree and other safety endpoints within 1 year. Subgroup analyses were conducted across different study types.Results A total of 510 participants fulfilling all eligibility criteria were enrolled in four studies. DES had a similar rate of any stroke or death within 1 month (3 studies, 476 participants: risk ratio (RR): 1.00; 95% CI: 0.46 to 1.11; p=1.00; I2=31%) to that of the BMS group and had a significantly lower rate of ISR within 1 year (4 studies, 429 participants: RR: 0.23; 95% CI: 0.13 to 0.41; p<0.001; I2=0%). Moreover, a lower rate of stroke recurrence within 1 year was reported (3 studies, 436 participants: RR: 0.46; 95% CI: 0.24 to 0.88; p=0.02; I2=52%) in the DES group.Conclusion This review demonstrates that the application of DES for intracranial stenting is safe and can significantly reduce the rates of ISR and recurrent ischaemic events. Further research is required to validate these results.PROSPERO registration number CRD42022338178.